Invention of space : city, travel and literature - Bou, Enric (Casa de la riqueza. Estudios de cultura de España, 2012)
Covering a wide range of topics and texts, "Invention of Space" explores ways in which space has been represented and recreated during the twentieth century in Spanish and Catalan literature.